2012
DOI: 10.4317/jced.50650
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Talon cusp in Indian population.

Abstract: Aim: To investigate the prevalence of the talon cusps in a sample of Indian dental patients and their distribution among different types of teeth. To determine the presence of other dental anomalies associated with the talon cusps. Method: 2740 out patients (1523 males and 1217 females) attending Oral Medicine department from November 2010 to January 2011 were screened for the presence of talon cusps and were subjected to Intra Oral Peri-apical (IOPA) radiograph to rule out any associated anomalies or peri-api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
4
9
0
3
Order By: Relevance
“…10 Talon's cusp was the second most commonly found anomaly with a prevalence of 0.5% in our study population. This is close to 0.93% as observed by Siddaih et al 11 and 0.58% as observed in the study by Prabhu et al 12 The presence of Talon's cusp may cause irritation of the tongue during Section: Dentistry function, compromise esthetics, occlusal interference may lead to cusp fracture, displacement of affected tooth, TMJ pain and traumatic bite. 12 The prevalence of Taurodontism (enlargement of tooth crown at the expense of root) was observed in 0.4% cases, which is close to 0.3% reported by Javali et al 10 and Sener et al 13 Supernumerary teeth or Hyperdontia is a freqent finding in dental practice and in our study it was found in 0.3% cases, which was similar to the findings of Deolia et al and close to 0.5% as observed by Salem G. 14 Most supernumerary tooth are impacted and usualy diagnosed incidentaly on radiographic examination.…”
Section: Discussionsupporting
confidence: 85%
“…10 Talon's cusp was the second most commonly found anomaly with a prevalence of 0.5% in our study population. This is close to 0.93% as observed by Siddaih et al 11 and 0.58% as observed in the study by Prabhu et al 12 The presence of Talon's cusp may cause irritation of the tongue during Section: Dentistry function, compromise esthetics, occlusal interference may lead to cusp fracture, displacement of affected tooth, TMJ pain and traumatic bite. 12 The prevalence of Taurodontism (enlargement of tooth crown at the expense of root) was observed in 0.4% cases, which is close to 0.3% reported by Javali et al 10 and Sener et al 13 Supernumerary teeth or Hyperdontia is a freqent finding in dental practice and in our study it was found in 0.3% cases, which was similar to the findings of Deolia et al and close to 0.5% as observed by Salem G. 14 Most supernumerary tooth are impacted and usualy diagnosed incidentaly on radiographic examination.…”
Section: Discussionsupporting
confidence: 85%
“…The talon cusp is usually seen on the palatal or lingual surfaces of the maxillary or mandibular anterior teeth, and very few cases have been reported about its presence on the facial aspect of tooth surface (5). The cusps predominantly occur on permanent maxillary lateral or central incisors and less frequently on mandibular incisors and maxillary canine (6). The case reported here highlights the rare presentation of talon cusp on the facial aspect of maxillary lateral incisor in a female patient.…”
Section: Introductionmentioning
confidence: 85%
“…Orthodontic management may be necessary in case of tooth displacement or malalignment of the same or opposite tooth. [5,14,15] The treatment modalities and preventive strategies so planned should revolve around the future complications or associated systemic diseases.…”
Section: Discussionmentioning
confidence: 99%